Traditional Intelligence of the Tenger Tribe Community in Viewing the Hazard of Mount Bromo Eruption - Dwi Rahmawati; Turniningtyas Ayu Rachmawati; Christia Meidiana (Eduvest - Journal of Universal Studies, 2022)
Mount Bromo is a volcano that erupts frequently and Sukapura District, Probolinggo Regency, was severely affected by the eruption. In addition, the community adheres to the local culture. This relationship affects hazard risk reduction efforts that must pay attention to the local culture. If it is not in accordance with local culture, then hazard risk reduction efforts cannot be implemented. Therefore, this research was conducted to explore local characters related to the threat of the eruption of Mount Bromo in order to obtain a reference basis for preparing an appropriate hazard management plan. This study aims to: 1) Mapping the vulnerability of Mount Bromo eruption in Sukapura Regency based on the community based on the IDW interpolation technique; 2) Develop a model of the influence and relationship of traditional intelligence variables on community-based Mount Bromo eruption vulnerability zoning using the SEM-PLS analysis technique. The results showed that the level of vulnerability to the eruption of Mount Bromo which was interpreted by the people of Sukapura District was influenced by the variables of physical semiotics, cultural semiotics, faunal semiotics and vegetal semiotics.